2019
DOI: 10.2355/tetsutohagane.tetsu-2018-088
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Local Deformation and Ductile Fracture Behaviors between Hard VC and Soft Cu Particle Dispersion Ferritic Steels

Abstract: Particle dispersion ferritic steels with hard VC carbide particles and that with soft Cu particles were tensile-tested for investigating the effect of particle nature (hard or soft) on plastic deformation and ductile fracture behaviors. The Cu dispersion steel exhibited a significantly larger necking deformation than the VC dispersion steel, which is due to less frequent void formation in the Cu dispersion steel. Digital image correlation (DIC) analysis for tensile-deformed specimens revealed that the plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…1) This finding contradicts the expectation that V addition induces homogeneous strain distribution. Through high-resolution DIC analysis, Tsuchiyama et al 7) revealed that strain concentration occurred around the VC precipitates. Therefore, although V addition leads to a decrease in the difference of strain between the ferrite and martensite phases, it causes inhomogeneous strain distribution in the ferrite phase.…”
Section: Resultsmentioning
confidence: 99%
“…1) This finding contradicts the expectation that V addition induces homogeneous strain distribution. Through high-resolution DIC analysis, Tsuchiyama et al 7) revealed that strain concentration occurred around the VC precipitates. Therefore, although V addition leads to a decrease in the difference of strain between the ferrite and martensite phases, it causes inhomogeneous strain distribution in the ferrite phase.…”
Section: Resultsmentioning
confidence: 99%
“…mens revealed that plastic strain was concentrated around the vanadium carbide particles. 9) However, the majority of previous studies using DIC have applied two-dimensional (2D) analysis. For a more precise understanding of deformation behavior, it is necessary to carry out analysis of strain distribution in two perpendicular planes and/or three dimensions in metals.…”
Section: Strain Distribution Analysis Of Two Perpendicular Planes In Sus310s Austenitic Stainless Steel Using Digital Image Correlationmentioning
confidence: 99%
“…Deformation behavior has been computationally investigated using the finite element method (FEM) [1][2][3] and, more recently, digital image correlation (DIC). [4][5][6][7][8][9][10][11] The latter is an innovative noncontact optical technique to measure the strain and displacement in metals.…”
Section: Introductionmentioning
confidence: 99%